Infections and nutrient deficiencies during infancy predict impaired growth at 5 years: Findings from the MAL-ED study in Pakistan - González-Fernández, Doris; Cousens, Simon; Rizvi, Arjumand; Chauhadry, Imran; Soofi, Sajid Bashir; Bhutta, Zulfiqar Ahmed (Frontiers in Nutrition, 2023)
Socio-economic, nutritional, and infectious factors have been associated with impaired infant growth, but how the presence of these factors during infancy affects growth around 5 years is not well understood. Methods: This secondary analysis of the MAL-ED cohort included 277 children from Pakistan for whom socio-demographic, breastfeeding, complementary foods, illness, nutritional biomarkers, stool pathogens and environmental enteropathy indicators between 0-11 months were recorded. We used linear regression models to analyze associations of these indicators with height-for-age (HAZ), weight-for-age (WAZ) and weight-for-height (WLZ) at 54-66 months (~5y), and Poisson regression with robust standard errors to estimate risk ratios for stunting and underweight ~5y, controlling for gender, first available weight, and income. Results: Among the 237 infants followed longitudinally and evaluated at about 5 years of age, exclusive breastfeeding was short (median= 14 days). Complementary feeding started before 6 months with rice, bread, noodles, or sugary foods. Roots, dairy products, fruits/vegetables, and animal-source foods were provided later than recommended (9-12 months). Anemia (70.9%), deficiencies in iron (22.0%), zinc (80.0%), vitamin A (53.4%) and iodine (13.3%) were common. Most infants (>90%) presented with diarrhea and respiratory infections in their first year. At ~5y, low WAZ (mean -1.91 ± 0.06) and LAZ (-2.11 ± 0.06) resulted in high prevalence of stunting (55.5%) and underweight (44.4%) but a relatively low rate of wasting (5.5%). While 3.4% had concurrent stunting and wasting ~5y, 37.8% of children had coexisting stunting and underweight. A higher income and receiving formula or dairy products during infancy were associated with a higher LAZ ~5y, but infant’s history of hospitalizations and more respiratory infections were associated with lower LAZ and higher risk of stunting ~5y. Infants’ intake of commercial baby foods and higher serum-transferrin receptors were associated with higher WAZ and lower risk of underweight ~5y. Presence of Campylobacter and fecal neopterin >6.8 nmol/L in the first year were associated with increased risk of underweight ~5y. Conclusions: Growth indicators ~5y were associated with poverty, inappropriate complementary feeding, and infections during the first year of life, which supports the early start of public health interventions for preventing growth delay ~5y.